Comparing Gonioscopy With Visante and Cirrus Optical Coherence Tomography for Anterior Chamber Angle Assessment in Glaucoma Patients. Issue 2 (February 2016) - Hu, Cindy X.; Mantravadi, Anand; Zangalli, Camila; Ali, Mohsin; Faria, Bruno M.; Richman, Jesse; Wizov, Sheryl S.; Razeghinejad, M. Reza; Moster, Marlene R.; Katz, L. Jay
Abstract : Purpose: The aim of this study was to compare gonioscopy with Visante and Cirrus optical coherence tomography (OCT) for identifying angle structures and the presence of angle closure in patients with glaucoma. A secondary objective was to assess interrater agreement for gonioscopy grading among 3 independent examiners. Methods: Gonioscopy grading using Spaeth Classification and determination of angle-closure risk was performed on 1 randomly selected eye for 50 phakic patients. Images of the same eye using both Visante and Cirrus OCT were obtained in both light and dark conditions. Agreement of angle closure among 3 devices and interrater agreement for gonioscopy were determined using Cohen's κ ( K ) or Kendall's coefficient of concordance ( W ). Results: Of the 50 patients, 60% were female, 64% were white, and the mean age was 62 years. Angle closure was detected in 18%, 16%, and 48% of quadrants with Visante, Cirrus, and gonioscopy, respectively. The scleral spur was identified in 56% and 50% of quadrants with Visante and Cirrus OCT, respectively. Visante and Cirrus OCT showed moderate agreement in detecting angle closure ( K =0.42 light, K =0.53 dark) but slight-to-fair agreement with gonioscopy (Visante K =0.25, Cirrus K =0.15). Gonioscopy demonstrated substantial agreement in angle closure ( K =0.65 to 0.68) and angle-closure risk assessment ( W =0.83) among 3 examiners. Conclusions: Visante and Cirrus OCT imaging may have limited ability to identify angle closure because of difficulty identifying angle structures. Gonioscopy by well-trained clinicians had remarkably consistent agreement for identifying angle-closure risk.